2007
DOI: 10.1021/pr060664t
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Serum Glycome Due to Metastatic Prostate Cancer

Abstract: Glycomic profiles derived from human blood sera of 10 healthy males were compared to those from 24 prostate cancer patients. The profiles were acquired using MALDI-MS of permethylated N-glycans released from 10-microL sample aliquots. Quantitative permethylation was attained using solid-phase permethylation. Principal component analysis of the glycomic profiles revealed significant differences among the two sets, allowing their distinct clustering. The first principal component distinguished the 24 prostate ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
250
4
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(262 citation statements)
references
References 46 publications
(104 reference statements)
5
250
4
3
Order By: Relevance
“…Recently, we have shown that fucosylation of PSA can be used to differentiate aggressive from nonaggressive prostate cancer (37). Altered fucosylated glycans have been reported in the serum glycome from 10 normal patients and 24 prostate cancer patients (38). However, the cause of the glycan changes was not clear in the previous reports.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, we have shown that fucosylation of PSA can be used to differentiate aggressive from nonaggressive prostate cancer (37). Altered fucosylated glycans have been reported in the serum glycome from 10 normal patients and 24 prostate cancer patients (38). However, the cause of the glycan changes was not clear in the previous reports.…”
Section: Discussionmentioning
confidence: 94%
“…Another study showed that inhibition of the glycosylation of EGFR and Met in glioma cells could significantly reduce the tumor growth, leading to an enhancement in tumor radiosensitivity [28]. Meanwhile, there are also many other high-throughput studies performed in efforts to find new markers of glycoproteins in various cancers [29][30][31]. All these researches have provided new insights into understanding the progression of cancer and possible markers for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic studies suggest a promising link between prostate cancer incidence and differential isoform expression in healthy and cancer patient sera (6,8,9). Although promising, rigorous validation studies are needed to translate the potential of protein isoforms to the clinic.…”
mentioning
confidence: 99%
“…Recent ELISA-based formats offer notable gains in analytical sensitivity (10,11). Nevertheless, mounting evidence suggests that protein isoform "fingerprinting" could advance diagnostic performance (6,9,12). Unfortunately, ELISA is severely limited for isoform discrimination because antibodies specific to protein isoforms often do not exist (12).…”
mentioning
confidence: 99%